Political parties and political development / edited by Joseph La Palombara and Myron Weiner - "Palombara, Joseph La. (ed.) (New Jersey, 1966)
In this sixth volume in its "Studies in political development " the committee on comparative politics of the social science research.
Keywords: Political Parties